A framework for Interlibrary-loan implementation (in one semester). Issue 1 (16th February 2015) - Irwin, John; Favaro, Sharon
Abstract : Purpose: – The purpose of this paper is to provide a framework for implementing and "going live" with a new interlibrary loan system (ILL), ILLiad Document delivery system and RAPID ILL, in one semester. Design/methodology/approach: – This paper provides a framework for implementing ILLiad and RAPID ILL through conducting a needs assessment, review of the existing practices and selection process of hardware/software, collaboration with stakeholders within the library and university for implementation, training and "going live". Findings: – This paper demonstrates how to implement a new interlibrary system in one semester. There are many benefits to implementing and "going live" in one semester. Staff training coupled with "going live" is essential to retain the new skill set and put it into practice. Finally, the most immediate and important impact of the new system was giving the university community (students and faculty) expanded access to collections and providing an overall better user experience. Originality/value: – This article provides a framework for other libraries to use as a model when considering implementing a new ILL system, such as ILLiad and RAPID ILL, in the course of one semester.